Pengaruh Kegagalan Fungsional, Kegagalan Sistem, Kegagalan Informasi Dan Kegagalan Layanan Terhadap Penggunaan M-Banking Serta Kaitannya Dengan Kepuasan Nasabah Bca Mobile Di Indonesia - Permatasari, Intan Ayu; Utami, Fitriani Nur (eProceedings of Management, 2024)
The rapid development of technology has become the main driver of the emergence of digital-based products andservices. One of the technology-based banking service products is mobile banking. In Indonesia, the mobile bankingthat has the most users is BCA Mobile. However, with the most users, the quality of BCA Mobile itself still oftencomplained about by its users. This study aims to determine how much influence functional failure, system failure,information failure, and service failure have on the use of BCA Mobile and its relationship with user satisfaction. Themethod used is quantitative method. The sampling technique uses SRS or simple random sampling with a sample sizeof 400 respondents who are BCA Mobile users in Indonesia. Data collection using a questionnaire distributed viaGoogle Form. The data analysis technique used is SEM - PLS with SmartPLS 4.0 software. The results of this studyindicate that functional failures, system failures, information failures, and service failures are in the "Good" category.Functional failure, information failure, and service failure have no effect on the use of BCA Mobile.Meanwhile, systemfailure has a negative and significant effect on the use of BCA Mobile.And the use of BCA Mobil affects usersatisfaction.Keywords-failure, mobile banking, satisfaction